Pelatihan Kepemimpinan Pengurus OSIS MA Hidayatullah Semarang - Hesti Rahmayanik; Harry Christiono (BADAN PENERBIT STIEPARI PRESS, 2022)
Leadership is a very important factor in achieving organizational success that has been determined, and to address the problems that exist in OSIS MA Hidayatullah Semarang, it is necessary to hold basic OSIS leadership training. Good basic leadership training will have an easier impact on the role of leadership style in making comprehensive decisions. The leaders are required to be enthusiastic about learning to understand the basics of leadership; in the future, it is hoped that the OSIS chairman will be able to display a good leadership style that is in line with the organization's goals. In addition, the training program aimed to shape students' character and personality in honing soft skills that could be useful after graduating and entering the workplace. The service carried out can provide an overview of the role of leadership style; with leadership training, it is hoped that it will equip students with the skills to lead an organization and make decisions within the organization.